Phoenix rising 2000: How Timor-Leste’s media bloomed from the ashes of violence and bloody conflict - Howarth, Bob (Pacific Journalism Review : Te Koakoa, 2018)
Commentary: The second annual Dili Dialogue Forum in July 2018 was sponsored by UNESCO, UNDP and the Timor-Leste Press Council and the governments of New Zealand, Japan and the Netherlands. Delegates came from Asian press councils and media freedom bodies, including the South East Asian Press Alliance, and from Cambodia, China, Hongkong, Indonesia, Japan, Philippines and Thailand. For the first time, Papua New Guinea’s Media Council was represented by its secretary and popular television presenter Belinda Kora. The author reflects on two days of presentations and roundtable discussions at the Forum—which saw Dili becoming the hub for a much bigger alliance of Asia-Pacific press councils—in the context of his long involvement in Timor-Leste media freedom issues.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjQxMzUvcGpyLnYyNGkyLjQ0OA